ANALISIS PORTOFOLIO PENDEKATAN CAPITAL ASSET PRICING MODEL (CAPM) DAN MODEL MARKOWITZ EFFICIENT PORTOFOLIO (MEP) SEBAGAI PREFERENSI INVESTOR TERHADAP PEMILIHAN SAHAM DI PASAR MODAL INDONESIA (Pendekatan shariah, Studi pada Indeks Saham LQ-45 dan Jakarta Islamic Index (JII) di Bursa Efek Indonesia) - Qurratul A’yun Nailufarh (BALANCE: Economic, Business, Management and Accounting Journal, 2008)
Portfolio investment is an investment in securities with the hope of obtaining some level of profits from investments made in the capital market. Shares will be chosen is a collection of optimal or efficient portfolio, ie, high risk high return. Analyzing the profitability of the investment required analytical methods portfolio (CAPM and MEP) to calculate the value of a good value investment return and value of the investment risk will be obtained and give a share to be used as an investment election. Investors can choose the level of portfolio return on the two stock indices, namely Jakarta Islamic Index (JII) that could be used as benchmark (benchmark) to measure the performance of an investment in the shares with the criteria of sharia, and LQ45 which have high liquidity. Capital Asset Pricing Model (CAPM) and Markowitz Efficient Portfolio (MEP) is a model developed to describe a state of balance between risk and return relationship each asset in portfolio investment when capital markets are in a state of balance, which is illustrated by a graph or curve method Security Market Line (SML), and the Efficient Frontier by using the Beta () and standard deviation () as a measure of risk in both models. By using two models of this analysis, the investor can estimate the expected return on securities in the JII and LQ45, stock portfolios can be identified by both, has a value of more investment, as a concept could also be a good investment election by the shariah and the investor can eliminate doubts in investing , because when buying and selling activity of these shares misused and become a tool for the pursuit of speculative profits at the expense of others, it is haraam because it turned into a gambling stock (maysir) and contain gharar. This can be used as consideration in the analysis of images of the two models in this research, both in the analytical model Capital Asset Pricing Model (CAPM) and Markowitz Efficient Portfolio (MEP). Keyword: CAPM, MEP, SML, Efficient Frontier, Analisis Gharar, Return, Risk